Monoterpenos dos óleos essenciais dos brotos e folhas de Araucaria angustifolia - Fernandes, Regina Rosa; Moreira, Eduardo Augusto; Miguel, Obdulio Gomes (Acta Biológica Paranaense, 1991)
Monoterpenos dos óleos essenciais dos brotos e folhas de Araucaria angustifolia